'Bogey Bogey Stuff': Gold Coastism, federation, and white backlash in Southern Rhodesia, 1951-56. Issue 2 (4th March 2022) - Marmon, Brooks
ABSTRACT: This article explores the apprehension white Rhodesians evinced towards the transformation of the Commonwealth and initial signs of African decolonisation, especially in colonial Ghana. Whites informally dubbed these undesired changes 'Gold Coastism'. Rhodesia's ruling party weaponised these fears and argued that a Central African Federation would preserve British influence and forestall African nationalism on Southern Rhodesia's borders. As it became clear this Federation would not significantly obstruct black African political activity, white fears of Gold Coastism accelerated. This resulted in a concerted push for independence and anti-British sentiment in Southern Rhodesia earlier than existing scholarship generally acknowledges.